Robust exponential stability of nonlinear impulsive switched systems with time-varying delays - Liu, Xiu; Zhong, Shouming; Ding, Xiuyong (Nonlinear Analysis: Modelling and Control, 2012)
This paper deals with a class of uncertain nonlinear impulsive switched systems with time-varying delays. A novel type of piecewise Lyapunov functionals is constructed to derive the exponential stability. This type of functionals can efficiently overcome the impulsive and switching jump of adjacent Lyapunov functionals at impulsive switching times. Based on this, a delay-independent sufficient condition of exponential stability is presented by minimum dwell time. Finally, an illustrative numerical example is given to show the effectiveness of the obtained theoretical results.
Keywords: impulsive systems; switched systems; minimum dwell time; exponential stability; delays